Bicompartmental locked bucket-handle tears of menisci concealing the concomitant anterior cruciate ligament injury for 2 years - a case report. - Zabrzynski, Jan; Szwedowski, Dawid; Zabrzyńska, Agnieszka; Łapaj, Łukasz (Journal of Medical Science, 2018)
Locked bucket-handle tears of both medial and lateral menisci, called in literature "Jack and Jill lesion", with simultaneous anterior cruciate ligament (ACL) injury is an extremely unusual phenomenon. It was reported only in a few cases in literature, which were unfortunately highly differentiated in the field of trauma mechanism, treatment options and postoperative care. Authors presented a clinical case of patient with a locked knee joint, by the torn both menisci, what masked the simultaneous ACL rupture and supremely imitated a stable joint. The locked knee is a clinical case demanding the urgent intervention to prevent further damages to the joint structures. Surprisingly, the patient after locking of the menisci and migration of their inner fragments to the intercondylar notch, started to feel the affected joint stabile and dismissed from the further treatment for next 2 years. Complex trauma needs a complex treatment, and a single-stage or multi-stage surgical approach is performed. Authors chose a two-steps surgical procedure with primary meniscal repair and secondary, early ACL reconstruction.